Towards sustainable green IT: motivations, issues and challenges / Hartini Abdul Jalil and Erne Suzila Kassim - Abdul Jalil, Hartini; Kassim, Erne Suzila (2014)
Climate change, carbon omission and other environmental issues such as footprint and resource constraint are becoming the world’s major concerns and need to be solved. Green Information Technology (IT) or by adapting IT appropriately has been suggested to reduce those problems and bring greater efficiency. It is important to analyses the awareness of IT Personnel about Green IT in order to measure whether they are ready to implement a Green IT strategy. Aimed using a qualitative case study research approach we seek to understand the motivations, issues and challenges for green IT initiatives and its usage from the context of government agencies in Malaysia. Interviews were conducted with several IT personnel from government agencies. A specific green IT initiative has being investigated with the implementation of data center cooling, virtualization, network and email consolidation. The study established that awareness level of green IT in Malaysia is low when compared with developed nations. The current findings suggest that although IT personnel In Malaysia have already some concerns about climate change and the power consumption of IT, there is still a lack of implementation and action dimensions. Therefore, further studies need to be carried out to find key success factors to increase the awareness level and strategy to implement Green IT.